International Countries' Responses to Donald Trump's Import Tariff Policy - Chuasanga, Anirut; Wahyudi, Trubus; Victoria, Ong Argo (Universitas Islam Sultan Agung, 2025)
This study uses a qualitative research method, This study is descriptive, and the methods used in this study use various methods, starting from collecting data related to the object of research, data analysis, and the data obtained is analyzed and interpreted into written form. So in this study, the qualitative method will be the basis for explaining Donald Trump's policy in raising import tariffs. Donald Trump is the 45th president of the United States who won over his rival Hillary Clinton from the Democrats in the United States presidential election. The economic policy of the United States during the Trump era is Protectionism, President Trump has made tariffs the mainstay of his economic strategy. He restored America's trade balance, reducing the gap between how much the US buys from other countries and how much the US sells to other countries. Trump has announced a series of new tariffs that include base tariffs for all countries as well as additional tariffs of varying amounts for each country. the impact of US tariffs on international trade: geopolitical changes and business opportunities, the impact of US tariffs on the global economy, geopolitics and the formation of new alliances, geopolitics and the formation of new alliances.